Local Communities Participation in Ecotourism Development - Kaharuddin Kaharuddin; Satyawan Pudyatmoko; Chafid Fandeli; Wisjnu Martani (Jurnal Ilmu Kehutanan)
The community forest Mandiri Kalibiru manages of protected forests one of activities is ecotourism management. The involvement of local communities as ecotourism actors is a major feature in the service business. This study aims to present the type of local communities participation in developing ecotourism, and the role of HKm institution in encouraging the local communities to participate in ecotourism. The concept of participation at the planning, implementation and utilization level is illustrated in three periods of tourism development: the first period-pioneering, the second-developing and the third-developed. Data collection uses in-depth interview techniques and document review. Data analysis was performed descriptively and theoretical propositions. There are differences in local communities participation in the three periods. Participation in the planning level is very dependent on the companion during periods 1 and 2, but when the third period, the planning can be done independently. Participation in the implementation level in periods 1 and 2 was carried out cooperatively, but in the third period, the implementation of the development uses professional staff. Participation in utilization rates began in the second period involving limited HKm members and youth leaders, and the 3rd period the Kalibiru community involved took advantage of work and business opportunities which reached 85%. The high local communities participation is inseparable from the role of partners, government and HKm institutional regulations in facilitating and providing of participating space for local communities.